Prevalence and factors associated with poor sleep quality among secondary school teachers in a developing country - Musa, Nor Asma; Moy, Foong Ming; Wong, Li Ping (National Institute of Occupational Safety and Health, 2018)
This study aimed to determine the prevalence and factors associated with poor sleep quality among secondary school teachers in the state of Selangor, Malaysia. This was a cross sectional study, conducted in two phases. Phase I tested the reliability of the Pittsburgh Sleep Quality Index in the Malay language (M-PSQI), whereas Phase II determined the prevalence and factors associated with poor sleep quality where a total of 1,871 secondary school teachers were studied. Participants were recruited using multistage sampling. Self-administered questionnaire was used to collect data on socio-demographic and teaching characteristics, comorbidities and characteristics of sleep. The M-PSQI was used to measure sleep quality. The Depression Anxiety Stress Scale-21 was used to measure mental health status. Results showed that the M-PSQI had a good internal consistency and moderate reliability. The prevalence of poor sleep quality was 61 (95% CI: 54–67)%. Total teaching hours/day, depression and stress were significantly associated with poor sleep quality in the univariate analysis, while only stress (OR 1.04; 95% CI 1.02–1.05%) remained significant in the multivariate analyses. In conclusion, stress level of the secondary school teachers should be reduced to improve sleep quality.